2021
DOI: 10.3390/ijms23010358
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Roles of Platelet and Coagulation Pathways in Collagen- and Tissue Factor-Induced Thrombus Formation

Abstract: In hemostasis and thrombosis, the complex process of thrombus formation involves different molecular pathways of platelet and coagulation activation. These pathways are considered as operating together at the same time, but this has not been investigated. The objective of our study was to elucidate the time-dependency of key pathways of thrombus and clot formation, initiated by collagen and tissue factor surfaces, where coagulation is triggered via the extrinsic route. Therefore, we adapted a microfluidics who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Next, we assessed whether JAQ1 binding would be affected by the pre-incubation of human platelets with different, established anti-huGPVI monoclonal antibodies (mAbs). Indeed, JAQ1-FITC binding was reduced by ~66% after pre-incubation with the function-blocking anti-huGPVI mAb EMF-1 [ 30 ], but only partially by the non-function-blocking EMF-2 (~26%) ( Figure 1 B). Subsequently, we tested whether JAQ1 recognizes huGPVI in a Western blot analysis of human platelet lysate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we assessed whether JAQ1 binding would be affected by the pre-incubation of human platelets with different, established anti-huGPVI monoclonal antibodies (mAbs). Indeed, JAQ1-FITC binding was reduced by ~66% after pre-incubation with the function-blocking anti-huGPVI mAb EMF-1 [ 30 ], but only partially by the non-function-blocking EMF-2 (~26%) ( Figure 1 B). Subsequently, we tested whether JAQ1 recognizes huGPVI in a Western blot analysis of human platelet lysate.…”
Section: Resultsmentioning
confidence: 99%
“…The heparin was purchased from Ratiopharm (Ulm, Germany). The JAQ1 [ 24 ], EMF-1 [ 30 ], EMF-2, JON/A [ 42 , 43 ] and WUG 1.9 were generated in house. The IV.3 antibody was purchased from Biozol (Eching, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In hemostasis and thrombosis, the generation of thrombin is in part triggered by vascular-exposed tissue factor. Kinetic studies with flowed blood have shown that the role of tissue factor in platelet aggregation and thrombus formation is only short-term [ 44 ]. Interestingly, one report states that this role of tissue factor can depend on factor VII-activating protein (FSAP, gene HAPP2 ).…”
Section: Thrombin Par1 and Par4 Receptor Stimulationmentioning
confidence: 99%
“…Recent multiparameter microfluidics assays have provided first understanding of the molecular mechanisms, implicated in whole-blood thrombus formation involving GPVI [ 10 , 11 , 12 ]. The heterogenous buildup of arterial thrombi takes place by a series of consecutive platelet activation events, i.e., flow-dependent platelet adhesion, integrin αIIbβ3 activation, granular secretion, platelet aggregation, and thrombus contraction and stabilization [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%